Learning types and learning success in a structured diabetes education programme for patients with type 2 diabetes: study protocol of a prospective, longitudinal study. Issue 8 (22nd August 2019) - Morro, Thimo; Fink, Astrid; Carmienke, Solveig; Frese, Thomas; Guenther, Sebastian
Abstract : Introduction: Diabetes mellitus (DM) has had a wide-ranging impact on healthcare politics. Secondary diseases and complications caused by diabetes are relevant cost and utilisation factors in the healthcare system. For decades, diabetes self-management education (DSME) has played a major role in the treatment of patients with type 2 DM (T2DM). The aim of this training is to empower patients to actively influence their diabetes process by gaining knowledge about health-related behaviours, such as healthy nutrition and exercise, and cardiovascular risks. The aim of the project is to analyse the practice of structured diabetes education and the effects of different learning types of participants. This project focuses on the needs of socioeconomically deprived patients and aims to improve DSME for this group. This patient group has a higher prevalence of T2DM, more complications and worse therapy-relevant parameters. Methods and analysis: The study will be conducted as a prospective longitudinal study. Patients will be recruited in outpatient physician offices over a period of 12 months. Patients will be included if they are 18 years and older, have T2DM and are scheduled to participate in DSME for the first time. A pseudonymised, written survey with standardised questionnaires will be administered. The data will be analysed using inferential statistical methods, such as correlation analysis, regression models and variance analytical designs. Ethics and dissemination: The study will be carried out following the principles of the Declaration of Helsinki and good scientific standards. Ethical approval of the Ethics Review Committee of the Medical Faculty at Martin-Luther-University, Halle-Wittenberg, was obtained. All participants in the study will receive comprehensive information and will be included after written informed consent is obtained. The results will be published in international peer-reviewed journals and presented at several congresses. Trial registration number: DRKS00016630